The ectomycorrhizal status of a tropical black bolete, Phlebopus portentosus, assessed using mycorrhizal synthesis and isotopic analysis - Kumla J. (2017)
© 2015, Springer-Verlag Berlin Heidelberg. Phlebopus portentosus is one of the most popular wild edible mushrooms in Thailand and can produce sporocarps in the culture without a host plant. However, it is still unclear whether Phlebopus portentosus is a saprotrophic, parasitic, or ectomycorrhizal (ECM) fungus. In this study, Phlebopus portentosus sporocarps were collected from northern Thailand and identified based on morphological and molecular characteristics. We combined mycorrhizal synthesis and stable isotopic analysis to investigate the trophic status of this fungus. In a greenhouse experiment, ECM-like structures were observed in Pinus kesiya at 1 year after inoculation with fungal mycelium, and the association of Phlebopus portentosus and other plant species showed superficial growth over the root surface. Fungus-colonized root tips were described morphologically and colonization confirmed by molecular methods. In stable isotope measurements, the δ 13 C and δ 15 N of natural samples of Phlebopus portentosus differed from saprotrophic fungi. Based on the isotopic patterns of Phlebopus portentosus and its ability to form ECM-like structures in greenhouse experiments, we conclude that Phlebopus portentosus could be an ECM fungus.